Verification of the formulation and efficacy of Danggui Buxue Tang (a decoction of Radix Astragali and Radix Angelicae Sinensis): an exemplifying systematic approach to revealing the complexity of Chinese herbal medicine formulae - Li Winnie; Zhao Kuijun; Cheung Anna; Ding Anwei; Duan Jinao; Cheung Jerry; Li Jun; Gao Qiutao; Dong Tina; Tsim Karl (BMC, 2007)
Abstract This article exemplifies a systematic approach to revealing the complexity of Chinese herbal medicine formulae through three levels of scientific research: standardization of herbs, verification of ancient formulae and mechanism studies. We use Danggui Buxue Tang (DBT) as an example for this approach. Among thousands of traditional Chinese medicine herbal formulae, almost all of which consist of multiple herbs, DBT is one of the simplest. Containing only two herbs, namely Radix Astragali (RA) and Radix Angelicae Sinensis (RAS), DBT is traditionally used to treat ailments in women. The weight ratio of RA to RAS in DBT was prescribed to be 5:1 as early as in 1247 AD. In addition to advanced chemical analysis of herbal constituents, DNA genotyping techniques have been developed for reliable standardization of RA and RAS. Chemical evaluation shows that main active constituents in DBT, including astragaloside IV, calycosin, formononetin and ferulic acid, were most abundant after extraction at the RA to RAS ratio of 5:1, whereas other tested RA to RAS ratios only gave sub-optimal levels of the active constituents. Biological evaluation indicates that bioactivities of DBT, e.g. immuno-modulatory, oesteotropic and estrogenic effects are also best exerted at the RA to RAS ratio of 5:1. Correlation analysis demonstrates statistically significant relationship between the tested chemical constituents and tested bioactivities. Up- and down-regulation of expression of some genes as potential biomarkers has been detected by using gene chip technology. This systematic approach on the basis of herbal standardization, chemical and biological verification and mechanism studies, as exemplified in this article, will be useful to reveal the complexity of not only DBT but also other Chinese medicine herbal formulae.